Review of the genus Eotilla Schuster, 1949 (Hymenoptera: Bradynobaenidae: Typhoctinae: Eotillini) and description of new species from Argentina - Torrens, Javier (2014)
Diagnoses for the genus Eotilla Schuster, 1949 based on males and females, new generic and specific characters, descriptions of two new Argentinian species (Eotilla schusteri Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov. and E. medanito Torréns, Fidalgo, Roig-Alsina & Brothers, sp. nov., based on both sexes), a description of the female of E. superba Brothers, 1974 and redescriptions of the males of E. mickeli Schuster, 1949 and E. superba are provided. A key to the species of Eotilla is presented.